Registro de enfermagem no prontuário em um hospital universitário: uma busca pela humanização do cuidado - Silva, Maria da Guia Feliciano da (2011)
T he aim of this study is to analyze the view of nurses about nursing records in the patient chart, in perspective of the record of humanized care. This is a case study, with qualitative approach. For its achievement, was sought and granted authorization from the direction of the Hospital Universitário Onofre Lopes (HUOL) and the Ethics Committee in Research of HUOL as Statement No. 422/10. During data collection, interviews were conducted with 20 nurses of the institution. The data analysis was based on the theoretical framework of Minayo to thematic content analysis, grounded in authors who work with themes, nursing records and quality care. With the empirical material, we constructed a framework of analysis, which was identified four categories thus nominated, "Reading and learning from those who register," "nursing records and quality of care," "the essence of nursing records" and "intention and action on the record of the subjective aspects of the patient." The results show that the records are insufficient, even in the case of the procedures performed with the patients often do not inform about the aspects that deal with the subjectivity that surround it, and admit that the records do not represent a parameter for evaluating the quality of care at least at that institution. In summary, the respondents recognize the importance of valuing subjectivity of the patient in their treatment, yet admit to neglect this aspect as significant for comprehensive health care, humane and quality